Accelerate Project Activities Of Systematic Land Complete Registration (PTSL) In Tigajuru Village, Mayong Subdistrict, Jepara District - Jawad Fadli; Umar Ma’ruf (Jurnal Akta, 2018)
This study aims to Investigate the implementation of PTSL activities in Tigajuru Village, Mayong Subdistrict, Jepara District and find out the barriers and solutions in the implementation of PTSL activities in Tigajuru Village, Mayong Subdistrict, Jepara District.The method used in this research is the Socio-Juridical. Data collection techniques using the data of primary and secondary data. Data were analyzed using qualitative analysis in order to obtain clarity on the issues discussed and subsequently prepared as a thesis of a scientific nature.Results of analysis showed that the stages of implementation of land registration systematically full of determining the location, the establishment of adjudication committee, counseling, the establishment of a task force of data collectors Juridical data collection Juridical, the data processing Juridical and evidentiary rights, edaphology and measurement, announcement, publishing certificate, and the final stage of delivery of certificates. Implementation of Land Registration of Property Rights Systematically full compliance with the Regulation of the Minister of ATR / BPN No. 1 of 2017 in Jepara, it is stipulated in the Regulation of the Minister of ATR / BPN No. 1 Of 2017 on the Acceleration of the Implementation of Systematic Land Complete Registration.Keywords: Accelerate Project; PTSL; Notary.